Soul of a nation art in the age of Black Power - Driskell, David C. 1931-2020; Gaither, Edmund B.; Goode-Bryant, Linda; Jarrell, Jae; Jarrell, Wadsworth 1929-; Lewis, Samella Sanders 1924- (Tate Publishing, 2017)
In the period of radical change that was 1963-1983, young black artists at the beginning of their careers in the USA confronted key questions and pressures. How could they make art that would stand as innovative, original, formally and materially complex, while also making work that reflected their concerns and experience as black Americans? This significant new publication, accompanying an exhibition at Tate Modern, surveys this crucial period in American art history, bringing to light previously neglected histories of twentieth-century black artists, including Sam Gilliam, Melvin Edwards, Jack Whitten, William T. Williams and Frank Bowling. This book features substantial essays from co-curators Mark Godfrey and Zoe Whitley, writing on abstraction and figuration respectively. It will also explore the art historical and social contexts with subjects including black feminism; AfriCOBRA and other artist-run groups; the role of museums in the debates of the period; and where visual art sat in relation to the Black Arts Movement
Published on the occasion of the exhibition "Soul of a Nation : Art in the Age of Black Power", held at Tate Modern, London, 12 July - 22 October 2017; Crystal Bridges Museum of American Art, Bentonville, Arkansas, 3 February - 23 April 2018; Brooklyn Museum, New York, 7 September 2018 - 3 February 2019. - Literaturverzeichnis Seite 254
Keywords: Nengudi, Senga -- 1943-; Geschichte 1900-2000; Geschichte 1958-1983; Rezeption; Black arts movement; Black power; Kunst; USA; Art, Black / Exhibitions; Black power / United States / Exhibitions; Art, American / 20th century / Exhibitions; Ausstellungskatalog; Ausstellungskatalog -- Brooklyn Museum -- 07.09.2018-03.02.2019 -- Brooklyn, NY; Ausstellungskatalog -- Crystal Bridges Museum of American Art -- 03.02.-23.04.2018 -- Bentonville, Ark.; Ausstellungskatalog -- Tate Modern -- 12.07.2017-22.10.2017 -- London; Bildband